Characteristics of cadence during continuous walking in daily life - Kunihiro Shiina; Atsushi Nakagomi; Chisato Mori; Kenichi Sakurai; Takahiro Tabuchi (Heliyon, 2024)
Despite the acknowledged relationship between the usual (preferred) walking speed (UWS) and health, there is currently no practical method available to reliably and accurately detect slight changes in UWS. This study aimed to explore whether either of the following two phenomena occurs during continuous daily walking in various periods: (a) Similarity between the most frequent cadences in the two periods. (b) The occurrence of the most frequent cadence in at least one of the two periods during the other period, with a frequency close to that of the most frequent cadence. In August 2021, invitations to participate in the study were extended via email to participants that took part in the Japan COVID-19 and Society Internet Surveys (JACSIS). A mobile phone application that collected step data during continuous walking was provided to the participants, and data were collected from December 1, 2021, to January 31, 2022. While 1022 participants installed the phone application, only 505 had measurement data for ten days or more in each of the two months of the study duration. The cadence during continuous walking was automatically measured daily from 05:00 to 21:00. Most participants exhibited at least one of the phenomena mentioned above, confirming a common, notably frequent, invariant cadence over time. Overall, this method allows for the identification of minor reductions and lower bounds of decline in UWS. This study illustrates the potential for tracking a decreasing trend in UWS. Early detection of a downward trend permits individuals to take timely remedial action, as recovery is relatively easy, and the confirmation of even a slight recovery bolsters recovery motivation.